Anhydrite‐Assisted Hydrothermal Metal Transport to the Ocean Floor—Insights From Thermo‐Hydro‐Chemical Modeling. Issue 7 (29th June 2020) - Guo, Zhikui; Rüpke, Lars H.; Fuchs, Sebastian; Iyer, Karthik; Hannington, Mark D.; Chen, Chao; Tao, Chunhui; Hasenclever, Jörg
Abstract: High‐temperature hydrothermal venting has been discovered on all modern mid‐ocean ridges at all spreading rates. Although significant strides have been made in understanding the underlying processes that shape such systems, several first‐order discrepancies between model predictions and observations remain. One key paradox is that numerical experiments consistently show entrainment of cold ambient seawater in shallow high permeability ocean crust causing a temperature drop that is difficult to reconcile with high vent temperatures. We investigate this conundrum using a thermo‐hydro‐chemical model that couples hydrothermal fluid flow with anhydrite‐ and pyrite‐forming reactions in the shallow subseafloor. The models show that precipitation of anhydrite in warming seawater and in cooling hydrothermal fluids during mixing results in the formation of a chimney‐like subseafloor structure around the upwelling, high‐temperature plume. The establishment of such anhydrite‐sealed zones reduces mixing between the hydrothermal fluid and seawater and results in an increase in vent temperature. Pyrite subsequently precipitates close to the seafloor within the anhydrite chimney. Although anhydrite thus formed may be dissolved when colder seawater circulates through the crust away from the spreading axis, the inside pyrite walls would be preserved as veins in present‐day metal deposits, thereby preserving the history of hydrothermal circulation through shallow oceanic crust. Key Points: We have developed a thermo‐hydro‐chemical model that reconciles high vent temperatures with high subseafloor permeabilities via precipitation reactions Subseafloor anhydrite and pyrite precipitations, analogous to hydrothermal chimneys, can significantly impact vent temperature High temperature metal‐rich fluids can flow through these chimney‐like structures to form massive sulfide deposits at the seafloor